The Weight of Trash: Teaching Sustainability and Ecofeminism by Asking Undergraduates to Carry Around Their Own Garbage - Fahs, Breanne (Radical Teacher, 2015)
This essay outlines a recent assignment I designed for an upper-division cross-listed women and gender studies/social justice and human rights course I teach called, “Trash, Freaks, and SCUM.” In the context of the students reading Edward Humes’ (2012) Garbology, the trash bag assignment asked that students carry around their trash for two 48-hour periods and that they present it to the class. While the first two day period assesses their actual trash output, students are asked to produce as little trash as possible for the second two day period. This assignment aims to make trash visible and to help students learn about climate change, sustainability, conspicuous consumption, and how their individual carbon footprint contributes to the “big picture” of environmental strain. I describe this assignment and its goals in this essay, followed by an assessment of its role in teaching about social justice, in order to underscore the importance of experiential learning with trash and to highlight how this assignment fits the mission of my courses on feminism and social justice.